Estudo da viabilidade de aplicação do transporte pneumático para abastecimento de sulfato de sódio em indústria de fibra de vidro - Almeida, Thales Rosado de (Universidade Federal de São Carlos, 2021)
Technology advances changed the way we approach fine powder loading within the industry. Efficient and focused on problem-solving, these solutions drastically reduced losses in industry activities. The purpose of this project is to investigate new solutions for sodium sulfate loading in a fiberglass plant, assessing safety, utilities, installation, maintenance, and operational impacts. Studies regarding modern sodium sulfate loading led to two scopes, structured for further understanding. One of them is an airoperated diaphragm pump, modified for fine powder pumping, while the other is a reallocation of an inactive blow tank. Each scope was analyzed concerning safety risks, start-up costs, and monthly expenses. Costs related to the initial situation were estimated in 198,25 R$/month, while the blow tank proposition had an projected cost of 102,86 R$/month and the AODD pump, 90,16 R$/month. Safety was handled by risk based process safety guidelines, whose results for risk managing was 440 for current sodium sulfate loading, 275 for the blow tank operation, and 110 in an AODD pump activity, the only one that requires no further action to mitigate risks. In the end, the AODD pump was chosen as the most viable, mainly because of its safety benefits.
Study of the feasibility of application of pneumatic transportation for the supply of sodium sulfate in the fiberglass industry
Keywords: Transporte Pneumático; Bomba de Diafragma Operada Por Ar; Análise de Segurança; Vaso de Pressão; Pneumatic conveying; Air-operated diaphragm pump; Safety analysis; Blow tank; ENGENHARIAS::ENGENHARIA QUIMICA